Selection for drought tolerance in Kabuli chickpea genotypes in Neyshabour region - ali Ganjeali; saeed Joveynipou; hassan porsa (پژوهش‌های حبوبات ایران)
In order to evaluate and selection of drought tolerant chickpea (Cicer arietinum L.) genotypes and to identify the best indices for drought tolerance, an experiment was conducted at Agricultural Research Station of Neyshabour during 2005-2006 growing season. In this study, 150 Kabuli chickpea genotypes from Mashhad Chickpea Collection of Ferdowsi University of Mashhad, were evaluated in Augmented Design for Preliminary Yield Trials with 6 controls (including drought-sensitive variety, current cultivars and local check). Quantitative drought tolerance and susceptibility indices such as stress tolerance index (STI), stress susceptibility index (SSI), mean productivity (MP), geometric mean productivity (GMP), tolerance index (TOL) and harmonic mean (HM) were estimated based on seed yield in stress and non stress conditions. There were significant differences among genotypes for drought tolerance indices except for TOL and SSI. The highest seed yield in stress condition was found in genotypes MCC302, MCC427, MCC352, MCC1, MCC50, MCC62, MCC118 and MCC423 with 960, 905, 638, 625, 609, 602, 592, and 581 kg/ha, respectively. The highest seed yield in non-stress condition was observed in genotypes MCC312, MCC380, MCC304, MCC50, MCC117, MCC427, MCC301 and MCC311 with 2185, 1856, 1820, 1636, 1622, 1567, 1520 and 1514 kg/ha, respectively. According to the results of regression analysis, MP, STI, GMP and HM indices in chickpea were the best indices for selection drought tolerant genotypes of chickpea. Based on these results, genotype numbers of MCC50, MCC352 and MCC427 are recommended as drought tolerant chickpea genotypes.